CONTAMINATION OF ARCTIC AIR AT 3 SITES DURING A HAZE EVENT IN LATE WINTER 1986 - DJUPSTROM, M; PACYNA, JM; Maenhaut, W.; WINCHESTER, JW; Li, S. M.; SHAW, GE (ATMOSPHERIC ENVIRONMENT PART A-GENERAL TOPICS, 1993)
Interpretation of simultaneous measurements at three stations in different parts of the Arctic suggests that during winter air masses are forced into the Arctic from Eurasia in a surge towards Alaska and further return over the North Pole towards the European Arctic. On some occasions direct flow of the Eurasian air masses was detected in the European Arctic. Simple statistical methods and dispersion modelling proved useful in studying source-receptor relationships in the Arctic.